Idealisasi Penjadwalan Proyek Bangunan Gedung dengan Teknik Miller - Sumarningsih, Tuti (Department of Civil Engineering, Diponegoro University, 2008)
Bar Chart, the other name of Gantt Chart, is one type of sheduling form thatÂ often used in construction project. The Bar Chart is usually completed with S Curve, that present the cumulative earned of work from time to time. The S Curve can be used to controlled the progress of work in any time. The analysis of Earned Value Concept, that analyze cost and time consumed of work simultaneously, is based on S Curve either. In many cases, the shape of S Curve is formed unless reffered to certain rule, so that the shape of letter â€œSâ€ some times too steep or too slope slightly. To improve the shape of S Curve, Miller introduced the concept of S Curve that composed from three mathematicâ€™s formulas. The three formulas that form three parts ofÂ the curve are y = 0,0225 x2, y = 1,5 x â€“ 25 , and y = - 125 + 4,5 x â€“ 0,0225 x2Â respectively. This curve is ideal, whereas the earned of the work in a certain unit time changes gradually, therefore meet the concept of resources levelling. Miller divided the duration of project excecution in three parts. Each part has a same length ofÂ periode. The study of different length of periode for three parts shows that S Curve is not ideal, proved by the fluctuation of earned of work in significant value.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Keywords : S Curve, Earned of Work, Resources LevellingPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3661[How to cite: Sumarningsih, T. (2008), Idealisasi Penjadwalan Proyek Bangunan GedungÂ dengan Teknik Miller, Jurnal Media Komunikasi Teknik Sipil, Tahun 16, No. 1, pp. 1-10]